2022
DOI: 10.1123/ijsnem.2022-0074
|View full text |Cite
|
Sign up to set email alerts
|

Creatine Monohydrate Supplementation, but not Creatyl-L-Leucine, Increased Muscle Creatine Content in Healthy Young Adults: A Double-Blind Randomized Controlled Trial

Abstract: Creatine (Cr) supplementation is a well-established strategy to enhance gains in strength, lean body mass, and power from a period of resistance training. However, the effectiveness of creatyl-L-leucine (CLL), a purported Cr amide, is unknown. Therefore, the purpose of this study was to assess the effects of CLL on muscle Cr content. Twenty-nine healthy men (n = 17) and women (n = 12) consumed 5 g/day of either Cr monohydrate (n = 8; 28.5 ± 7.3 years, 172.1 ± 11.0 cm, 76.6 ± 10.7 kg), CLL (n = 11; 29.2 ± 9.3 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 24 publications
(35 reference statements)
0
6
0
Order By: Relevance
“…Participants were split into two groups: one received 5 g of Cr monohydrate daily and the other a PLA. The trial lasted 14 days [12]. After 14 days, the result showed that Cr monohydrate administration increased muscle Cr content [12].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Participants were split into two groups: one received 5 g of Cr monohydrate daily and the other a PLA. The trial lasted 14 days [12]. After 14 days, the result showed that Cr monohydrate administration increased muscle Cr content [12].…”
Section: Discussionmentioning
confidence: 99%
“…The trial lasted 14 days [12]. After 14 days, the result showed that Cr monohydrate administration increased muscle Cr content [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…
We have addressed the scientifically relevant points put forth by Escalante & St. Mart (2023), and we appreciate the opportunity to put their comments on our study (Askow et al, 2022) in proper context to the readers of your journal. In the following, we have provided our responses to Escalante & St.
…”
mentioning
confidence: 99%
“…
Recently, an article by Askow et al (2022) was published ahead of print in the journal on August 25, 2022. Researchers in this study recruited 29 participants and had them consume 5 g/day of either creatine monohydrate (CM), creatyl-l-leucine (CLL), or a placebo for 14 days in a randomized, double-blind design.
…”
mentioning
confidence: 99%